Multimodal cohesion in persuasive discourse: A case study of televised campaign advertisements in the 2020 US presidential election. (October 2021) - Schubert, Christoph
Highlights: Multimodal cohesion supports the persuasive objective of televised political advertising. Visual images, spoken words, and written text fulfil different cohesive functions. A lack of cohesion in one mode can be compensated for in another mode. Political ads foreground the candidate and his agenda and polarize public opinion. Abstract: This case study points out the ways in which multimodal texture contributes to the dominant persuasive function of political advertising discourse. It is based on a dataset of 27 televised advertisements by the Democratic presidential candidate Bernie Sanders, aired during the primary election period between October 2019 and March 2020. A qualitative approach is adopted, combining methods of political discourse analysis and multimodal approaches to cohesion. As an investigation of conjunctive relations between words and images shows, the three dominant modes in this type of mediatized political discourse serve complementary and mutually reinforcing functions: the spoken words in the advertisements typically constitute the central cohesive chain, while written captions on the screen highlight selected political keywords and slogans, and the visual images illustrate and exemplify the line of arguments. On this basis, it is shown that multimodal cohesion supports the three pivotal persuasive strategies of foregrounding the candidate, propagating the political agenda, and polarizing public opinion.